LEADERSHIP STYLES AND QUALITY OF WORK LIFE AMONG ADMINISTRATIVE STAFF AT A PUBLIC UNIVERSITY IN SARAWAK - Leviana Andrew; Siti Fatimah Abdul Latiff; Satriani Burhan (Journal of Islamic, Social, Economics and Development, 2019)
: Today’s organizations need effective leaders who understand the complexities of the rapidly changing global environment that leads to a better organizational performance. The authority to lead not to be in the person, different organizational culture existed, lack of the leadership attributes, and role overload were the dilemmas experienced by the leader. This study utilized a correlational quantitative design with 85 administrative staff at selected departments and faculties at a public university in Sarawak. The aim of the study is to identify to what extent the leadership styles practiced by the top management that affect the quality of work life as well as to examine the relationship between leadership styles and quality of work life among the administrative staff. These responses were collected by using the Multifactor Leadership Questionnaire (MLQ) and the Quality of Work Life (QWL) Questionnaire. The findings revealed that both transformational leadership style and transactional leadership styles are correlated with the quality of work life indicating positive, strong, and significant relationships. The study also found that both transactional and transformational leadership styles were practiced by the top management at selected departments and faculties in this university. Therefore, it is important to understand the type of leadership styles practiced since it will affect employees’ quality of work life. Apart from that, management can use these findings to assist leaders to improve their leadership skills as well as can shaping effective leader in such a way as to enhance employees’ quality of work life.